The tribological performances of Super Olein as fluid lubricant using four-ball tribotester. (February 2019) - Zulhanafi, P.; Syahrullail, S.
Abstract: One of the major problem of using palm oil as lubricant is the sustainability towards the oxidation reaction. In this study, double fractionated palm olein (SPL) was used as lubricant while Tertiary-Butyl-Hydroquinone (TBHQ) was used as anti–oxidant agent. Four-ball tribotester was used to determine the coefficient of friction, wear scar diameter and surface roughness. The results revealed that the additional TBHQ exhibited reduction in coefficient of friction and provide a smooth surface roughness. However, it was unable to prolong the protection on the metal surface by the metallic soap film thus resulted larger wear scar diameter. The physical appearances of wear worn were also discussed in details in this study. Highlights: The anti-oxidant agent (tbhq) was added to the palm olein based lubricant at 450PPM. The presence of tbhq reduced the oxidation effects of palm olein based lubricant. Palm olein based lubricant promoted lower coefficient of friction. Palm olein based lubricant exhibited smoother surface roughness.